Development and validation of the Distracting Ingenuity Promotion Scale for paediatric nurses to support the psychological outcomes of paediatric patients and their families: A survey‐based cross‐sectional cohort study - Hiroyuki Ogihara (Wiley, 2022)
Abstract Aim To develop and validate the Distracting Ingenuity Promotion Scale (DIPS) for paediatric nurses. Design Cross‐sectional study using anonymized self‐administered questionnaires. Methods From July-November 2013, paediatric nurses working in the wards or outpatient departments in 39 medical institutions in Japan were enrolled in the survey. Data were analysed using the Student's t‐test, Mann-Whitney U test and analysis of variance test. Exploratory and confirmatory factor analyses were performed to validate the factors in the DIPS. Cronbach's α was used to calculate the reliability of the DIPS. Results The DIPS included five subscales comprising 21 items. The goodness‐of‐fit indices for confirmatory factor analysis had a Comparative Fit Index of 0.923 and a Root Mean Square Error of Approximation of 0.059 and fulfilled the standard external validity criteria. Cronbach's α was 0.707-0.826 for each subscale and 0.895 for the overall scale.